METODE ALTERNATIF DALAM MENENTUKAN SOLUSI PARTIKULAR PERSAMAAN EULER-CAUCHY - Kiftiah, Mariatul; Yudhi, Yudhi; Yanitami, Alvi (BAREKENG: Jurnal Ilmu Matematika dan Terapan, 2021)
Euler-Cauchy equation is the typical example of a linear ordinary differential equation with variable coefficients. In this paper, we apply the alternative method to determine the particular solution of Euler-Cauchy nonhomogenous with polynomial and natural logarithm form. An explicit formula of the particular solution is derived from the use of an upper triangular Toeplitz matrix. The study showed that this method could be finding the particular solution for the Euler-Cauchy equation